Pelatihan SIPORSI (Sistem Pelaporan Terintegrasi) untuk Peningkatan Pengetahuan dan Keterampilan Pencatatan Kasus Tuberkulosis di Puskesmas Pembantu Kelurahan Serangan (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2025)
Kelurahan Serangan Sub-Health Center (Pustu) lacks a structured Tuberculosis (TB) case recording system, causing difficulties in reporting and contact investigation. This community service activity aims to improve health workers' knowledge and skills in TB case recording using SIPORSI (Integrated Reporting System) based on Google Spreadsheet. Implementation method included training with lectures, demonstrations, and hands-on practice for 5 hours conducted on October 4, 2025. Participants consisted of 4 Pustu health workers evaluated using pre-post test with 30 questions covering 5 knowledge domains. Results showed significant knowledge improvement from average score of 60% (pre-test) to 80% (post-test) with N-Gain Score of 0.50 (moderate category). SIPORSI knowledge domain showed the highest improvement of 66.7%. Participant satisfaction rate reached 90% with highest aspects on material relevance (95%) and hands-on practice opportunities (95%). This activity successfully improved health workers' competence in using SIPORSI for more structured TB case recording and supporting contact investigation.
Keywords: Training; SIPORSI; Tuberculosis; Google Spreadsheet; Sub-health center